Pengembangan Buku Nonteks Berbasis Riset Karakterisasi Salak Padangsidimpuan (Salacca Sumatrana Becc.) - Rahma, Aisyah; Hasairin, Ashar; Idramsa, Idramsa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to produce a non-textbook product about the development of a non-textbook based on research into the characterization of Salak Padangsidimpuan (Salacca Sumatrana Becc.). This study uses research and development (R&D) methods with the 4D Thiagarajan development model, which includes the stages of definition, design, development, and dissemination. The results of the study indicate that product validation by content experts obtained a score of 89.1%, categorized as